Respons Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) terhadap Perlakuan Priming PEG dalam Mengatasi Cekaman Salinitas - Salsabila Prasma Aisy; Diah Rachmawati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Salinity is an abiotic stress that can reduce the productivity of plants such as chili. Chili is a plant that has a low tolerance to salinity. Priming is a method of improving seed quality that can improve seed performance. One type of solution that is often used in priming is PEG (Polyethylene Glycol). This research was conducted to determine the concentration of PEG priming that gave the highest yield, and its effect on the growth of chili plants grown in salinity stress. This study used a factorial randomized block design (RBD), with 2 treatment factors and 6 replications. The first factor was the priming treatment of seeds with PEG 6000 which consisted of 3 levels, including: P0 (control), P1 (12.5% PEG), and P2 (25% PEG). The second factor was the treatment of salinity stress (NaCl) which consisted of 3 levels, namely: N0 (control), N1 (2000 ppm), and N2 (4000 ppm). Data analysis in this study used one-way analysis of variance (One-Way Analysis of Variance) and two-way (Two-Way Analysis of Variance). If the results show a significant effect, it will be continued by testing the difference between the treatment means with Duncan's Multiple Range Test at the 95% confidence level. The results showed that 25% PEG concentration was the concentration that gave the highest yield, and could increase the germination and growth of chili plants, such as: plant height (133.27 cm), number of leaves (327 strands), root fresh weight (48.18 gram), crown fresh weight (161.47 gram), root dry weight (17.63 gram), and shoot dry weight (37.65 gram) grown under conditions of salinity stress.